A self-powered power conditioning IC for piezoelectric energy harvesting from short-duration vibrations - Darmayuda, I Made (2013)
This brief presents a piezoelectric vibration power conditioning integrated circuit for energy autonomous sensor applications. The proposed circuit includes a negative voltage converter, a noninverting buck-boost converter working in discontinuous conduction mode (DCM), and a switching clock generator. Optimum load resistance is synthesized by the DCM buck-boost converter to achieve maximum power extraction, and system conduction loss is reduced by a novel arrangement of a current rectification diode within the buck-boost converter. This circuit is able to harness power from short-duration vibration and self starts up with a minimum 0.9-V input voltage. The proposed circuit has been implemented in a standard 0.18-μm CMOS process with 0.05-mm2 active area and achieved a maximum power conversion efficiency value of 54%.